Florence Nightingale on social change in India - Nightingale, Florence, 1820-1910 (Nightingale, Florence, 1820-1910. Collected works of Florence Nightingale ;, 2007)
Social Change in India shows the shift of focus that occurred during Florence Nightingale's more than forty years of work on public health in India. While the focus in the preceding volume, Health in India, was top-down reform, notably in the Royal Commission on the Sanitary State of the Army in India, this book documents concrete proposals for self-government, especially at the municipal level, and the encouragement of leading Indian nationals themselves. Famine and related epidemics continue to be issues, demonstrating the need for public works like irrigation and for greater self-help meas.